Is disclosure of information technology (IT) internal control weaknesses worthwhile for firms? - Kusumaningtias, Rohmawati; Kasim, Narimah; Handayani, Susi; Bhilawa, Loggar (Institute of Advanced Scientific Research, 2020)
This study investigated the effect of disclosing internal control weaknesses in implementing information technology and the mediating effect of intellectual capital (IT-ICW) on the value of information technology companies. The population in this study was companies in Southeast Asia that were listed on the New York Stock Exchange (NYSE) during the period 2006–2017. The data were analysed using a partial least square method. The results showed that IT-ICW affected the value of the company. The ccapital employed and the human capital strengthened the positive link between IT-ICW and the value of the company, while structural capital had no mediating effect. Intellectual capital is an intangible asset of a company. This paper describes the relationship between changes in information technology and corporate value and the mediating effect of intellectual capital. The readiness of intellectual capital for dealing with rapid technological changes can be seen in the changes in corporate value.